Facing the Music: Rituals of Belonging and Recognition in Contemporary Western Art Music - El-Ghadban, Yara (American Ethnologist, 2009)
In this article, I examine the tense relationship between belonging and recognition that occurs as two young composers try to situate their musical identities between the urge to contest the hegemony of Western art music and the desire to be part of and recognized within this musical tradition. I draw on their participation as finalists in an international composition competition to examine how issues of identity, postcoloniality, and belonging, on the one hand, and of musical authorship, subjectivity, and agency, on the other hand, are woven into the highly ritualized processes of evaluation and recognition in contemporary Western art music.

Une histoire du jazz à Montréal - Gilmore, John (Lux Éditeur, 2009)
Pendant près d’un demi-siècle (1920–1970), Montréal a été un centre névralgique du jazz en Amérique du Nord. Le légendaire nightlife de la ville et l’abondance de travail qu’il offrait attiraient des musiciens de tout le continent. Dans ce livre, John Gilmore décrit l’effervescence culturelle de cette époque. Il nous transporte à Montréal, après la tombée de la nuit, dans les lieux mythiques aujourd’hui presque tous disparus où ont vécu et joué les Myron Sutton, Johnny Holmes, Oscar Peterson, Louis Metcalf, Steep Wade, Maury Kaye et René Thomas. Dans cette contribution fondamentale à l’histoire du jazz, on découvre que les Noirs américains venus s’établir à Montréal au début du XXe siècle ont largement contribué à la culture populaire nord-américaine. Gilmore souligne qu’au-delà des réalisations individuelles des musiciens, la production du jazz a été profondément influencée par des facteurs politiques, sociaux et économiques : la prohibition et la ségrégation raciale aux États-Unis, l’essor économique – notamment du secteur ferroviaire – de Montréal puis la Grande Dépression des années 1930, la Seconde Guerre mondiale, le « nettoyage » de la ville et la renaissance de la « moralité civique » des années 1950 et, enfin, l’émergence de l’indépendantisme québécois.
Keywords: Art / General; History / Canada / Post-Confederation (1867-); Music / Genres & Styles / Jazz; Political Science / General

‘People Didn’t Call It Klezmer’: Klezmer Music in Jewish Montreal 1924-1970 - Lam, Emily (Student Journal of Canadian Jewish Studies, 2009)

‘Small Has No Inside, Big Has No Outside’: Montreal’s Chinese Diaspora Breaks Out/In Music - Morris, Kim Chow (MUSICultures, 2009)
Through ethnographic fieldwork undertaken from 2003 to 2010, discussion with local musicians, and analysis of concert programs, recordings, live performances, rehearsals, press reviews, musicians’ websites and textual sources, the author examines the means by which the Chinese diasporic community in Montreal negotiates its cultural identity and exerts its agency through musical performance. The author also explores how the tangled relationships of regionally- diverse Chinese immigrants to their birthplaces and their chosen homeland are unravelled, reflecting simultaneous positions as “insiders” and “outsiders.”